2013
DOI: 10.1039/c3tb20277a
|View full text |Cite
|
Sign up to set email alerts
|

Invitro and in vivo study of sustained nitric oxide release coating using diazeniumdiolate-doped poly(vinyl chloride) matrix with poly(lactide-co-glycolide) additive

Abstract: Nitric oxide (NO) is an endogenous vasodilator as well as natural inhibitor of platelet adhesion and activation that can be released from a NO donor species, such as diazeniumdiolated dibutylhexanediamine (DBHD/N2O2) within a polymer coating. In this study, various Food and Drug Administration approved poly(lactic-co-glycolic acid) (PLGA) species were evaluated as additives to promote a prolonged NO release from DBHD/N2O2 within a plasticized poly(vinyl chloride) (PVC) matrix. When using an ester-capped PLGA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 59 publications
(99 citation statements)
references
References 46 publications
(78 reference statements)
5
94
0
Order By: Relevance
“…Gaseous nitric oxide treatments and NO releasing materials have been used topically and shown to increase dermal blood flow, increase reepithelialization and angiogenesis, and accelerate wound repair; however, some of these studies have been conducted with uninfected wounds [41-45]. Previous studies have shown NO can be released from polymer films doped with diazeniumdiolate dibutylhexanediamine (DBHD/N 2 O 2 ), which releases NO through proton or thermal driven mechanisms [46-49]. However, the loss of NO from DBHD/N 2 O 2 creates free lipophilic amine species within the polymer that react with water, thereby increasing the pH within the polymer phase and effectively turning off the NO release.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gaseous nitric oxide treatments and NO releasing materials have been used topically and shown to increase dermal blood flow, increase reepithelialization and angiogenesis, and accelerate wound repair; however, some of these studies have been conducted with uninfected wounds [41-45]. Previous studies have shown NO can be released from polymer films doped with diazeniumdiolate dibutylhexanediamine (DBHD/N 2 O 2 ), which releases NO through proton or thermal driven mechanisms [46-49]. However, the loss of NO from DBHD/N 2 O 2 creates free lipophilic amine species within the polymer that react with water, thereby increasing the pH within the polymer phase and effectively turning off the NO release.…”
Section: Introductionmentioning
confidence: 99%
“…However, the loss of NO from DBHD/N 2 O 2 creates free lipophilic amine species within the polymer that react with water, thereby increasing the pH within the polymer phase and effectively turning off the NO release. In a recent report, poly(lactic-co-glycolic) acid was used as an additive to promote and prolong the NO release from poly(vinyl chloride) films doped with DBHD/N 2 O 2 [49, 50]. The ester linkages of the PLGA will hydrolyze in the presence of water, producing lactic and glycolic acids that can act as proton sources to promote the NO release from DBHD/N 2 O 2 -doped polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 This data is consistent with previously reported animal data, where it was shown that NO release is not compromised due to blood exposure. 31,33 The hemocompatibility of these catheters likely could be further improved by exploring methods to increase the NO flux from the SNAP/E2As polymer, perhaps by adding polymeric additives that increase the degree of water uptake by the E2As polymer.…”
Section: Evaluation Of Thrombus Formation and Bacterial Adhesion On Cmentioning
confidence: 99%
“…24,[27][28][29] NO-releasing polymers have been shown to preserve platelet count and reduced thrombus formation when tested in a 4 h rabbit model of extracorporeal circulation (ECC) thrombogenicity. [30][31][32][33][34] I-nitrosothiol-modified xerogels were shown to significantly reduce adhesion of platelets and bacteria (Pseudomonas aeruginosa) when tested in vitro. 35,36 Diazeniomdiolate-doped poly(lactic-co-glycolic acid)-based films exhibited antibiofilm properties against both gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria when tested using a drip-flow bioreactor over a 7 d period.…”
Section: Introductionmentioning
confidence: 99%